A new riparian species of Ramalina (Ramalinaceae) from Brazil, with a key to neotropical saxicolous species. (26th September 2018) - GUMBOSKI, Emerson Luiz; ELIASARO, Sionara; SCUR, Mayara Camila; LORENZ-LEMKE, Aline Pedroso; BORGES DA SILVEIRA, Rosa Mara
Abstract: The new species Ramalina fleigiae from Brazil is described growing on rocks in riverbeds in high altitude grasslands of southern Brazil. It grows in areas with constant water flow, sometimes almost immersed, and always in exposed habitats. Through an integrative approach, the detailed description of R. fleigiae includes morphological, anatomical, ecological, chemical and molecular data. Ribosomal DNA-based phylogenies suggest that R. fleigiae is more closely related to a species that shares its habitat preference ( R. laevigata ) than to the morphologically and chemically similar R. exiguella and R. gracilis. Ramalina fleigiae and R. laevigata can be distinguished by thallus morphology (irregularly flat branches in R. fleigiae vs. flat to canaliculate in R. laevigata ) and pattern of chondroid tissue, as genetic distances between them are compatible with the interspecific range. It is possible that many species of Ramalina still remain hidden within the morphological or chemical variation of currently accepted species. Combining ecological, anatomical and molecular data will improve our future understanding of this genus.